PERBEDAAN PENGETAHUAN IBU-IBU TENTANG ISU-ISU LINGKUNGAN ANTARA STRATEGI PENYULUHAN OUT GROUP VERSUS IN GROUP BERDASARKAN KEPEDULIAN LINGKUNGAN - Robert Zachariasz (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2016)
The objective of this research is to analyze the effect of extension strategy and the environmental concern on knowledge about environmental issues of house wives on the slums in West Jakarta. The sample of the research was 40 housewives, which selected randomly. The data were analyzed by using ANOVA with 2 x 2 factorial design. The result of the research reveals that: 1) the knowledge about environmental issues of housewiveswho received extension strategy by out group extension agents have not more highly than when they received extension by in group extension agents; 2) The housewives who have high environmental concern and receive extension by out group extension agents have more highly knowledge about environmental issues than when they received extension by in group extension agents; 3)The housewives who have low environmental concern and received extension by out group extension agents have lower knowledge about environmental issues than when they received extension by ingroup extension agents; 4) There are interaction effects between extension strategy and the environmental concern towards the housewives knowledge about environmental issues.